2021
DOI: 10.1101/2021.06.16.21258861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 seroprevalence among Vancouver public school staff in British Columbia, Canada

Abstract: Importance: Contact-tracing studies suggest minimal secondary transmission in schools. However, there are limited school data accounting for asymptomatic cases, particularly late in the 2020/21 school year, and in the context of uninterrupted in-person schooling and widespread community transmission. Objectives: To determine the SARS-CoV-2 seroprevalence in a sample of school staff, compared to the community, and to COVID-19 rates among all students and staff within the same school population. Design: Incident… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…While our study is one of the largest studies to report seroprevalence estimates in the student population in the later phase of the pandemic, the results are in line with a seroprevalence study in teachers showing no differences compared to a matched sample of blood donors [ 23 ] or to register data showing only minimal consequences for overall transmission if schools are kept open [ 12 ]. The regional differences in seroprevalence also support this finding.…”
Section: Discussionsupporting
confidence: 83%
“…While our study is one of the largest studies to report seroprevalence estimates in the student population in the later phase of the pandemic, the results are in line with a seroprevalence study in teachers showing no differences compared to a matched sample of blood donors [ 23 ] or to register data showing only minimal consequences for overall transmission if schools are kept open [ 12 ]. The regional differences in seroprevalence also support this finding.…”
Section: Discussionsupporting
confidence: 83%
“…To date we have published one report from our study that described seroprevalence in the first wave of the pandemic ( 7 ). Other Canadian serosurveys have been carried out over limited time periods and relied on blood spots for serology ( 11 , 12 ) or have been limited to specific regions ( 13 , 14 ) and/or populations ( 15 17 ). In other countries, such as the United States, blood donors are central to national monitoring of infections and vaccine seroprevalence ( 5 , 18 ) but have not published data on vaccine-related antibody concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Human resources data obtained from the 2 out of the 3 participating school districts show that the age and sex of respondents to the current vaccine survey were representative of the target population (target population had a mean age of 46.4 yrs and 73.6% were female). The sample was also previously reported to be representative of the target population based on geographical residence and COVID-19 positivity ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, approximately 17% of eligible school district staff participated in the present study; however, the study was designed to capture a representative sample of district staff within a short and defined time period and had a high response rate (95.4%) among participants of the parent seroprevalence study. In addition, we found that the study sample was representative of the target population on age, sex, geographical residence and COVID-19 infection rates ( 12 ), although selection bias related to other criteria may influence vaccine intentions. Second, the current study focused on intentions to receive the first dose of the COVID-19 vaccines and it is not known how intentions may differ toward the second or subsequent doses or how emerging news of side effects (e.g., risk of blood clots) may impact hesitancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation